The Relationship Between Recruitment, Training, Organizational Commitment, and Job Satisfaction on Employee Productivity (Case Study at Kosasih Urip Clinic, Bandar Lampung) - Gaeldeba Garaika; Abdul Halik; Siti Mujanah (Jurnal Multidisiplin Sahombu, 2025)
This study aims to examine the relationship between recruitment, training, organizational commitment, and job satisfaction on employee productivity. A quantitative approach was employed, with data collected through questionnaires distributed to employees within the relevant sector. The results reveal that selective recruitment, effective training programs, and high levels of organizational commitment positively influence job satisfaction and significantly enhance employee productivity.